CsSyllabusLOR: Computer Science Syllabus Learning Object Repository - Dave, Mona G; Virparia, PV (International Journal of Computer Sciences and Engineering, 2019)
Adaptable Educational Learning Object Repository (AELOR) for the subject of computer science has been proposed for the educational institutions and the educators to enable the access to different Learning Objects (LO). AELOR shall enhance the reusability and interoperability of LOs, while taking benefit of the granularity and aggregation features. This Learning Object Repository (LOR) will also give educators the chance to design a new syllabus from the existing courses which includes one or many Los. CsSyllabusLOR provides a platform for creating, collecting, retrieving learning objects and also suggesting Computer Science syllabi to the educator. The Educators and Learners from the Computer Science Educational community will be benefited by the syllabus learning object repository. In this paper, we have tried to propose an architecture of Syllabus Learning Object Repository for the subject of Computer Science.